A Cosmos in Stone: Interpreting Religion and Society Through Rock Art - Lewis-Williams, David J. (Rowman & Littlefield Publishers, 2002)
J. David Lewis-Williams is world renowned for his work on the rock art of Southern Africa. In this volume, Lewis-Williams describes the key steps in his evolving journey to understand these images painted on stone. He describes the development of technical methods of interpreting rock paintings of the 1970s, shows how a growing understanding of San mythology, cosmology, and ethnography helped decode the complex paintings, and traces the development of neuropsychological models for understanding the relationship between belief systems and rock art. The author then applies his theories to the famous rock paintings of prehistoric Western Europe in an attempt to develop a comprehensive theory of rock art. For students of rock art, archaeology, ethnography, comparative religion, and art history, Lewis-Williams' book will be a provocative read and an important reference.